2001
DOI: 10.1101/lm.29401
|View full text |Cite
|
Sign up to set email alerts
|

A Neural Circuit Analysis of Visual Recognition Memory: Role of Perirhinal, Medial, and Lateral Entorhinal Cortex

Abstract: Using a continuous recognition memory procedure for visual object information, we sequentially presented rats with eight novel objects and four repeated objects (chosen from the 8). These were selected from 120 different three-dimensional objects of varying sizes, shapes, textures, and degree of brightness. Repeated objects had lags ranging from 0 to 4 (from 0 to 4 different objects between the first and repeated presentation). An object was presented on one side of a long table divided in half by an opaque Pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 38 publications
1
27
0
Order By: Relevance
“…Rats receiving lidocaine infusions into the Prh failed to direct more exploration at novel objects than familiar objects, yet did not exhibit any grossly observable behavioral abnormalities or altered overall amounts of object exploration. This pattern of behavior suggests that Prh inactivation specifically blocked capacity for familiarity discrimination, which agrees with other demonstrations of impairments after permanent Prh lesions in similar spontaneous object recognition tasks (Ennaceur et al, 1996;Aggleton et al, 1997;Ennaceur and Aggleton, 1997;Bussey et al, 1999;Liu and Bilkey, 2001;Mumby et al, 2002) and in reinforced tests of object recognition memory (Mumby and Pinel, 1994;Kesner et al, 2001;Murray and Richmond, 2001). The basis for impaired familiarity discrimination in the present study cannot be determined but could relate to the hypothesized role of the Prh in either object recognition memory per se (i.e., the ability to remember that an object has been previously encountered), object identification (i.e., the ability to perceive diverse object features as an integrated whole distinct from other similar objects) or both (Murray and Richmond, 2001).…”
Section: Prh Contributions To Object Memorysupporting
confidence: 76%
“…Rats receiving lidocaine infusions into the Prh failed to direct more exploration at novel objects than familiar objects, yet did not exhibit any grossly observable behavioral abnormalities or altered overall amounts of object exploration. This pattern of behavior suggests that Prh inactivation specifically blocked capacity for familiarity discrimination, which agrees with other demonstrations of impairments after permanent Prh lesions in similar spontaneous object recognition tasks (Ennaceur et al, 1996;Aggleton et al, 1997;Ennaceur and Aggleton, 1997;Bussey et al, 1999;Liu and Bilkey, 2001;Mumby et al, 2002) and in reinforced tests of object recognition memory (Mumby and Pinel, 1994;Kesner et al, 2001;Murray and Richmond, 2001). The basis for impaired familiarity discrimination in the present study cannot be determined but could relate to the hypothesized role of the Prh in either object recognition memory per se (i.e., the ability to remember that an object has been previously encountered), object identification (i.e., the ability to perceive diverse object features as an integrated whole distinct from other similar objects) or both (Murray and Richmond, 2001).…”
Section: Prh Contributions To Object Memorysupporting
confidence: 76%
“…Evidence for hippocampal involvement in object recognition has been reported, although it is unclear whether the evidence is attributable to the length of the delay to test (Clark et al 2000;Hammond et al 2004) or when the lesions are performed relative to the initial encounter (Gaskin et al 2003). For both scenarios it was proposed that extrahippocampal structures, such as the perirhinal cortex, mediate the behavior in the absence of the hippocampus, a possibility that is supported by lesion data (Kesner et al 2001).…”
Section: Discussionmentioning
confidence: 60%
“…Recent studies demonstrate that the delay length determines hippocampal involvement (Hammond et al, 2004), and this is crucial for object recognition at a longer delay (hours), similar to what we studied here. However, we do acknowledge that associated structures like perirhinal and postrhinal cortex may influence ORT performance (Bussey et al, 1999;Kesner et al, 2001), and alterations in these brain regions could contribute to the changes observed in the young tau-P301L mice.…”
Section: Discussionmentioning
confidence: 99%